Uji Efektivitas Pemberian EKstrak Biji Pepaya (Carica papaya L.) Terhadap Pertumbuhan Rambut Kelinci (Oryctolagus cuniculus (Linnaeus,1758)) - Ayu Meilani; Mohammad Kanedi; Yulianty Yulianty; Nuning Nurcahyani (Balitbangda Provinsi Lampung, 2019)
Hair is one of the important parts of the human body that has many functions, one of the mainproblems of hair that many people experience is hair loss. To find a solution for the problem of hair loss, a very much natural ingredients can be used to stimulate hair growth. One of the natural ingredients that can be used to stimulate hair growth is papaya seeds. This study discusses the effects of extracts of papaya seed (Carica papaya L.) with a concentration of the most effective hair growth rabbit (Oryctolagus cuniculus (Linnaeus, 1758)). Variations of treatment used is the negative controls (K-) spread with distilled water, the positive control(K+) spread with minoxidil 2%, treatment 1 (P1) smeared gel extract of papaya seeds 5% concentration, treatment 2 (P2) smeared gel extract of papaya seeds concentration 10%, treatment 3 (P3) gel smeared papaya seed extract 15%, and treatment 4 (P4) gel smeared papaya seed extract concentration of 20%. Based on the results of further analysis of variance and LSD test at 5% significance level indicates that the gel seed extract of papaya (Carica papaya L.) to give effect to accelerate the growth of hair length but was not significantly different from the hair mass. The best treatment is at a concentration of 15% (P3).